Stress distribution patterns at mini-implant site during retraction and intrusion-a three-dimensional finite element study - Gautham Sivamurthy; Shantha Sundari (SpringerOpen, 2016)
Abstract Background The purpose of this study was to evaluate the stress patterns produced in mini-implant and alveolar bone, for various implant dimensions, under different directions of simulated orthodontic force, using a three-dimensional finite element method. Methods Eight finite element (FE) models of mini-implant and bone were generated with insertion angles of 30° and 60°, diameters of 1 and 1.3 mm, and lengths of 6 and 8 mm. A simulated constant orthodontic force of 2 N was applied to each of these FE models in three directions simulating anterior retraction, anterior intrusion and retraction, and molar intrusion. Results Comparison of the maximum von Mises stress in the mini-implant showed that the 1-mm diameter produced significantly high stress, and the amount of stress produced was more for a mini-implant inserted at an angle of 60°. The cortical bone showed that high stresses were generated for the 1-mm-diameter mini-implant and on increasing the insertion angulation from 30° to 60°, the stress produced increased as well. The comparison of von Mises stress in the cancellous bone was insignificant as the amount of stress transmitted was very low. Conclusions The 1-mm-diameter mini-implants are not safe to be used clinically for orthodontic anchorage. The 1.3 × 6 mm dimension mini-implants are recommended for use during anterior segment retraction and during simultaneous intrusion and retraction, and the 1.3 × 8 mm dimension mini-implant is recommended for use during molar intrusion. All mini-implants should be inserted at a 30° angle into the bone for reduced stress and improved stability.